Hypofractionated Stereotactic Radiotherapy for the Treatment of Benign Intracranial Meningiomas: Long-Term Safety and Efficacy - Eric K. Nguyen; Gregory R. Pond; Jeffrey N. Greenspoon; Anthony C. Whitton; Crystal Hann (Current Oncology, 2021)
Introduction: Hypofractionated stereotactic radiotherapy (hSRT) has emerged as an alternative to single-fraction stereotactic radiosurgery (SRS) and conventionally fractionated radiotherapy for the treatment of intracranial meningiomas (ICMs). However, there is a need for data showing long-term efficacy and complication rates, particularly for larger tumors in sensitive locations. Methods: A retrospective review was conducted on adult patients with ICMs seen at a tertiary care center. Eligible patients were treated with the CyberKnife platform and had a planned treatment course of 3–5 fractions from 2011–2020. The local control was assessed based on radiographic stability and the late toxicity/radionecrosis rates were recorded. Radiographic progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan–Meier method. Results: In total, 62 patients (age 26–87) with 67 treated tumors were included in this study with a median follow-up of 64.7 months. RT was delivered as the primary treatment in 62.7% of cases and for recurrence in 37.3%. The most common tumor locations were the convexity of the brain and the base of the skull. The tumor sizes ranged from 0.1–51.8 cc and the median planning target volume was 4.9 cc. The most common treatment schedule was 18 Gy in 3 fractions. The five-year PFS and OS were 85.2% and 91.0%, respectively. The late grade III/IV toxicity rate was 3.2% and the radionecrosis rate was 4.8%. Conclusions: Based on our data, hSRT remains an effective modality to treat low-grade ICMs with acceptable long-term toxicity and radionecrosis rates. hSRT should be offered to patients who are not ideal candidates for SRS while preserving the benefits of hypofractionation.